Early antibiotic exposure and development of asthma and allergic rhinitis in childhood - Jeffrey Ni; Hannah Friedman; Bridget C. Boyd; Andrew McGurn; Piotr Babinski; Talar Markossian; Lara R. Dugas (BMC, 2019)
Abstract Background The prevalence of pediatric allergic diseases has increased rapidly in the United States over the past few decades. Recent studies suggest an association between the increase in allergic disease and early disturbances to the gut microbiome. The gut microbiome is a set of intestinal microorganisms that begins to form during birth and is highly susceptible to disturbance during the first year of life. Early antibiotic exposure may negatively impact the gut microbiota by altering the bacterial composition and causing dysbiosis, thus increasing the risk for developing childhood allergic disease. Methods We performed a retrospective chart review of data in Loyola University Medical Center's (LUMC) Epic system from 2007 to 2016. We defined antibiotic exposure as orders in both the outpatient and inpatient settings. Inclusion criteria were being born at LUMC with at least two follow up visits. Asthma and allergic rhinitis diagnoses were obtained using ICD 9 and ICD 10 codes. We controlled for multiple confounding factors. Using Stata, bivariate logistic regression was performed between antibiotics from 0 to 12 months of life and development of disease. This analysis was repeated for total lifetime antibiotics. We defined statistically significant as p < .05. Results The administration of antibiotics within the first 12 months of life was significantly associated with lifetime asthma (OR 2.66; C. I 1.11-6.40) but not allergic rhinitis. There was a significant association between lifetime antibiotics and asthma (OR 3.54; C. I 1.99-6.30) and allergic rhinitis (OR 2.43; C. I 1.43-4.11). Conclusion Antibiotic administration in the first year of life and throughout lifetime is significantly associated with developing asthma and allergic rhinitis. These results provide support for a conservative approach regarding antibiotic use in early childhood.